Social and Economic Development and Change in 4 Guatemalan Villages Over a Half Century. Issue 1 (June 2020) - Melgar, Paúl; Maluccio, John A.; Arevalo, Aura Isabel; Alvarez, Andrea; Alvarez, Marvin
This article describes nearly 50 years of social and economic development and changes that have occurred in the 4 villages of the Institute of Nutrition of Central America and Panama (INCAP) Longitudinal Study (1969-1977). In doing so, it contextualizes the changes in health and nutrition for the study population over that period. Since the start of the INCAP Longitudinal Study, the original 4 villages, like their home country, have undergone tremendous demographic, social, and economic change. Originally rather isolated, road and transportation access for the villages has improved steadily and substantially. The population in the villages has more than doubled. Schooling access and outcomes have also improved substantially, with average grades of schooling tripling and literacy doubling, reaching levels currently on par with national averages. Occupations have also changed over the course of a generation. Early on, subsistence farming and agriculture in general were dominant but are now much less common. Much of this change is associated with declining agricultural markets alongside increased access to nonagricultural jobs near the villages and in the capital. With all these changes have come improvements in living standards. It is within this dynamic context that study participants for the INCAP Longitudinal Study were born and raised and where most now live as adults.